2013
DOI: 10.1016/j.econmod.2013.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Do countries belonging to the same region suggest the same growth enhancing variables? Evidence from selected South Asian countries

Abstract: We investigate the growth enhancing variables in a group of countries belonging to the same geographical area namely, India, Sri Lanka, Pakistan and Bangladesh over the period 1960-2010. We find that this "homogeneity" does not necessarily imply that countries have the same growth enhancing variables due mainly to differences in institutions and policies. Our result suggests that time-series econometrics are preferable to identify the growth drivers for a country accurately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
0
3
0
1
Order By: Relevance
“…Bhattacharjee and Haldar (2015a, 2015b) in their study under the purview of NGT have undertaken panel data analysis and observed the negative insignificant influence of political stability in the four major economies of South Asia. Cooray et al (2013) show, by employing appropriate statistical tests, that despite apparent homogeneity in countries belonging to the same geographical area with similar technology and apparently similar macro stylized facts, there could be other sources of heterogeneity such as different national policies or political, legal and economic institutions that may change the focus. They argue that this makes time-series estimation techniques more suitable for growth driving variables.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Bhattacharjee and Haldar (2015a, 2015b) in their study under the purview of NGT have undertaken panel data analysis and observed the negative insignificant influence of political stability in the four major economies of South Asia. Cooray et al (2013) show, by employing appropriate statistical tests, that despite apparent homogeneity in countries belonging to the same geographical area with similar technology and apparently similar macro stylized facts, there could be other sources of heterogeneity such as different national policies or political, legal and economic institutions that may change the focus. They argue that this makes time-series estimation techniques more suitable for growth driving variables.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The growth-led import (GLI) model and export-import-led model are relevant for all countries in the sample. Cooray et al (2013) show employing appropriate statistical tests, that despite apparent homogeneity in countries belonging to the same geographical area with similar technology, and apparent similar macro stylized facts, there could be other sources of heterogeneity such as different political, legal and economic institutions, and national policies that may change the focus. Ahmed and Krishnasamy (2013) have adopted the meta-frontier framework to analyse the technological gap and level of catch-up of the three regions in Asia, namely, Southern Asia, Eastern Asia and ASEAN5 with respect to the Asian technology as a whole for the period 1980-2006.…”
mentioning
confidence: 99%
“…Further, it is relevant to highlight that many South Asian countries have striking similarities. Mallik and Chowdhury (2001); Cooray, Paradiso, and Truglia (2013) argue that Pakistan, Sri Lankan, Bangladesh and India can be considered a homogenous group of countries on the basis of economic performance, economic characteristics, structure of output, technology, culture, education, and capital accumulation. The fact that a similar study does not exist in the South Asian region, our results have thus relevance to a broad range of countries, not just Pakistan.…”
Section: Introductionmentioning
confidence: 99%